Environmental Bottlenecks on Children's Genetic Potential for Adult Socioeconomic Attainments: Evidence from a Health Shock - Jason M. Fletcher (Institute of Labor Economics (IZA), 2018)
This paper explores gene-environmental interactions between family environments and children's genetic scores in determining educational attainment. The central question is whether poor childhood family environments reduce the ability for children to leverage their genetic gifts to achieve high levels of educational attainments. The multigenerational information and genetic data contained in the Health and Retirement Study is used to separate two mechanisms of intergenerational transmission of socioeconomic status – genetic endowments and family environments. Using parental in utero exposure to the 1918/1919 influenza pandemic as a source of quasi-experimental variation to family environments (but not affecting children's genetic endowments), this paper estimates interactions between parental investments and children's genetic potential. The main finding suggests that girls with high genetic potential whose fathers were exposed to influenza face reduced educational attainments – a gene-environment interaction – but there is no similar effect for boys.
Keywords: J62; J1; J24; 330; in utero exposure; gene-environment interactions; polygenic score; intergenerational effects